Technology engagement is associated with higher perceived physical well-being in stroke patients prescribed smartwatches for atrial fibrillation detection - Mensah Otabil, Edith; Dai, Qiying; Anzenberg, Paula; Filippaios, Andreas; Ding, Eric; Mehawej, Jordy; Mathew, Joanne E.; Lessard, Darleen; Wang, Ziyue; Noorishirazi, Kamran; Hamel, Alexander; Paul, Tenes; et al. (Frontiers in Digital Health, 2023)
Background: Increasing ownership of smartphones among Americans provides an opportunity to use these technologies to manage medical conditions. We examine the influence of baseline smartwatch ownership on changes in self-reported anxiety, patient engagement, and healthrelated quality of life when prescribed smartwatch for AF detection.We performed a post-hoc secondary analysis of the Pulsewatch study (NCT03761394), a clinical trial in which 120 participants were randomized to receive a smartwatch-smartphone app dyad and ECG patch monitor compared to an ECG patch monitor alone to establish the accuracy of the smartwatch-smartphone app dyad for detection of AF. At baseline, 14 days, and 44 days, participants completed the Generalized Anxiety Disorder-7 survey, the Health Survey SF-12, and the Consumer Health Activation Index. Mixed-effects linear regression models using repeated measures with anxiety, patient activation, physical and mental health status as outcomes were used to examine their association with smartwatch ownership at baseline.: Ninety-six participants, primarily White with high income and tertiary education, were randomized to receive a study smartwatch-smartphone dyad. Twenty-four (25%) participants previously owned a smartwatch. Compared to those who did not previously own a smartwatch, smartwatch owners reported significant greater increase in their self-reported physical health (b = 5.07, P<0.05), no differences in anxiety (b =0.92, P=0.33), mental health (b =-2.42, P=0.16), or patient activation (b = 1.86, P=0.54).Participants who own a smartwatch at baseline reported a greater positive change in self-reported physical health, but not in anxiety, patient activation, or self-reported mental health over the study period.